SOCIAL ENTREPRISES IN ROMANIA - Daniela PIRVU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The concept of social economy concept is relatively new in Romania, but the interest of specialists and practitioners is growing because significant funds has been allocated to stimulate the development of social economy organizations and numerous supporting statements was made by the European Commission. The present paper realizes an exploratory approach on the concept of social enterprise in Romania and clarifies some notions, given the practices of social economy in recent years. Also, a typology of the Romania's counties in terms of the presence of social enterprises has been obtained. A series of data were collected by accessing sites of specialized institutions or requesting information under the Law regarding the free access to information of public interest. After their processing a territorial distribution of social enterprises in Romania was shaped.